Detection of human papillomavirus in laryngeal squamous cell carcinoma: systematic review and meta-analysis - Gama, Ricardo Ribeiro Gama (2016)
Background: Recent studies have reported a human papillomavirus (HPV) prevalence of 20% to 30% in laryngeal squamous cell carcinoma (LSCC), although clinical data on HPV involvement remain largely inconsistent, ascribed by some to differences in HPV detection methods or in geographic origin of the studies. Objective To perform a systematic review and formal meta-analysis of the literature reporting on HPV detection in LSCC. Methods Literature was searched from January 1964 until March 2015. The effect size was calculated as event rates (95% confidence interval [CI]), with homogeneity testing using Cochran's Q and I2 statistics. Meta-regression was used to test the impact of study-level covariates (HPV detection method, geographic origin) on effect size. Potential publication bias was estimated using funnel plot symmetry. Results One hundred seventy nine studies were eligible, comprising a sample size of 7,347 LSCCs from different geographic regions. Altogether, 1,830 (25%) cases tested HPV-positive considering all methods, with effect size of 0.269 (95% CI: 0.242 to 0.297; random-effects model). In meta-analysis stratified by the 1) HPV detection technique and 2) geographic study origin, the between-study heterogeneity was significant only for geographic origin (P = .0001). In meta-regression, the HPV detection method (P = .876) or geographic origin (P = .234) were not significant study-level covariates. Some evidence for publication bias was found only for studies from North America and those using non–polymerase chain reaction methods, with a marginal effect on adjusted point estimates for both. Conclusions Variability in HPV detection rates in LSCC is explained by geographic origin of study but not by HPV detection method. However, they were not significant study-level covariates in formal meta-regression.